THE LIVING HADITH PHENOMENON IN BANJAR SOCIETY: Integrating Ritual Devotion and Social Solidarity in the Al-Ma’sum Majelis Dhikr and Syarikat Kematian (RIWAYAH, 2025)
This study aims to analyze the practices of the Majelis Dhikr and Syarikat Kematian Al-Ma’sum at the Al-Ma’sum Mosque in Barabai, Banjar, as a representation of the Living Hadith phenomenon within the Banjar community. Utilizing a qualitative-descriptive approach, this research explores how Prophetic traditions are internalized into local customs to fortify both spiritual and social dimensions. The findings demonstrate that the integration of collective dhikr rituals every Wednesday night with an organized funeral assistance system creates a harmony between the dimensions of hablun min Allah (relationship with God) and hablun min al-nas (relationship among humans). The practice of "7 Laksa" dhikr, distributed proportionally among members, is not merely an eschatological ritual but serves as an instrument to cultivate inner tranquility and moral discipline. Concurrently, the Syarikat Kematian functions as a social institution that mitigates the economic burden on bereaved families through self-funded contributions. This study contributes theoretically to the sociology of Islam by offering a model of how mosque institutions can transform into strategic social capital. Furthermore, it asserts that the contextualization of Islamic values into local Banjar culture does not reduce the essence of religious teachings; rather, it strengthens their relevance and continuity in facing contemporary social dynamics. Through the synthesis of ritual devotion and collective responsibility, the Al-Ma’sum Assembly successfully reinforces communal solidarity (ukhuwah) and resilience within the framework of a living tradition.[Penelitian ini bertujuan untuk menganalisis praktik Majelis Dzikir dan Syarikat Kematian Al-Ma’sum di Masjid Al-Ma’sum, Barabai, Banjar sebagai representasi fenomena Living Hadis dalam masyarakat Banjar. Dengan menggunakan pendekatan kualitatif-deskriptif, penelitian ini mengeksplorasi bagaimana hadis Nabi diinternalisasi ke dalam tradisi lokal untuk memperkuat dimensi spiritual sekaligus sosial. Hasil menunjukkan bahwa integrasi ritual zikir kolektif setiap malam Rabu dengan sistem bantuan pemulasaraan jenazah yang terorganisir menciptakan harmoni antara dimensi hablun min Allah (hubungan dengan Tuhan) dan hablun min al-Nas (hubungan antarsesama). Praktik zikir 7 Laksa yang didistribusikan secara proporsional kepada anggota bukan sekadar ritual eskatologis, melainkan instrumen untuk memupuk ketenangan batin dan disiplin moral. Sementara itu, Syarikat Kematian berfungsi sebagai institusi sosial yang memitigasi beban ekonomi keluarga dhuafa melalui iuran swadaya. Penelitian berkontribusi teoretis terhadap sosiologi Islam dengan menawarkan model bagaimana institusi masjid dapat bertransformasi menjadi modal sosial (social capital) yang strategis, sekaligus menegaskan bahwa kontekstualisasi nilai-nilai Islam ke dalam budaya lokal Banjar tidak mereduksi esensi ajaran agama, melainkan memperkuat relevansi dan kontinuitasnya dalam menghadapi dinamika sosial kontemporer. Melalui sintesis antara pengabdian ritual dan tanggung jawab kolektif, Majelis Al-Ma’sum berhasil memperkokoh solidaritas (ukhuwah) dan resiliensi komunitas dalam bingkai tradisi yang hidup.]